TIME SERIES ANALYSIS ON OCEAN WAVE HEIGHT USING EXPONENTIAL MOVING AVERAGE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The attributes of the nature are directly or indirectly affects each other; one of its causes was the ocean waves that are commonly generated by the wind. This wave sometimes affects the coastal areas and marine life. The sea waves are considerable with the time and space which can be represented in terms of mathematics. So, the analysis of ocean waves can give knowledge to predict the upcoming waves. The main objective of this paper is to study and analysis of ocean waves with help of exponential moving average.